Causal attributions and the trolley problem. (17th November 2021) - Sytsma, Justin; Livengood, Jonathan
ABSTRACT: In this paper, we consider two competing explanations of the empirical finding that people's causal attributions are responsive to normative details, such as whether an agent's action violated an injunctive norm – the counterfactual view and the responsibility view . We then present experimental evidence that uses the trolley dilemma in a new way to investigate causal attribution. In the switch version of the trolley problem, people judge that the agent ought to flip the switch, but they also judge that she is more responsible for the resulting outcome when she does so than when she refrains. As predicted by the responsibility view, but not the counterfactual view, people are more likely to say that the agent caused the outcome when she flips the switch.